Basic diagnostics and assessment of the technical condition of reinforced concrete tanks intended for storing drinking water - Abel, Tomasz (Instal, 2021)
The subject of the article are selected issues in the field of diagnostics, technical condition assessment and repair guidelines for reinforced concrete water tanks constituting elements of the water supply network. The discussed issue is the problem of maintaining the objects in question in proper technical condition and the related periodic diagnostics of their condition. The primary source of knowledge on the technical condition of reinforced concrete tanks are direct inspections and inspections carried out during technological breaks.